The Long-Term Outcome of Boys With Partial Androgen Insensitivity Syndrome and a Mutation in the Androgen Receptor Gene - GÜRAN, TÜLAY (ENDOCRINE SOC, 2016)
Background: In boys with suspected partial androgen insensitivity syndrome (PAIS), systematic evidence that supports the long-term prognostic value of identifying a mutation in the androgen receptor gene (AR) is lacking. Objective: To assess the clinical characteristics and long-term outcomes in young men with suspected PAIS in relation to the results of AR analysis. Methods: Through the International Disorders of Sex Development Registry, clinical information was gathered on young men suspected of having PAIS (n = 52) who presented before the age of 16 years and had genetic analysis of AR. Results: The median ages at presentation and at the time of the study were 1 month (range, 1 day to 16 years) and 22 years (range, 16 to 52 years), respectively. Of the cohort, 29 men (56%) had 20 different AR mutations reported. At diagnosis, the median external masculinization scores were 7 and 6 in cases with and without AR mutation, respectively (P =.9), and median current external masculinization scores were 9 and 10, respectively (P =.28). Thirty-five men (67%) required at least one surgical procedure, and those with a mutation were more likely to require multiple surgeries for hypospadias (P =.004). All cases with an AR mutation had gynecomastia, compared to 9% of those without an AR mutation. Of the six men who had a mastectomy, five (83%) had an AR mutation. Conclusions: Boys with genetically confirmed PAIS are likely to have a poorer clinical outcome than those with XY DSD, with normal T synthesis, and without an identifiable AR mutation. Routine genetic analysis of AR to confirm PAIS informs long-term prognosis and management.
Keywords: SEX DEVELOPMENT; HORMONE-LEVELS; DISORDERS; MEN; TESTOSTERONE; DISEASE; BINDING; HYPOSPADIAS; INHIBITION; FERTILITY